Photocatalytic C−H Amination of Electron‐rich Aromatic Hydrocarbons by Carbon Nitride Photocatalysis. Issue 5 (31st January 2023) - Mazzanti, Stefano; Markushyna, Yevheniia; Savateev, Oleksandr
Abstract: Construction of C−N bond is a central process in organic synthesis. Typically, it relies on noble‐metal catalysts and prefunctionalized substrates, such as aryl halides. Alternative and more appealing method is a direct C−H amination of hydrocarbons that is based on intrinsic reactivity of the in situ generated radical cations, which are more electrophilic compared to their closed‐shell precursors. In this work, we employ potassium poly(heptazine imide) (K‐PHI), a graphitic carbon nitride semiconductor, to enable C−H amination of electron rich aromatic hydrocarbons with NH3 and pyrazole under oxidative conditions. Screening of oxidants, indicate those molecules that are able to accept not only electrons, but also protons, such as O2, PhNO2 and Ph2 S2, mediate the reaction. As such, multisite proton‐coupled electron transfer (MS‐PCET) from the photocharged state of K‐PHI to the acceptor of electrons and protons is the key element in the studied photocatalytic process. Abstract : Carbon nitride photocatalyst for organic synthesis : A graphitic carbon nitride, potassium poly(heptazine imide) (K‐PHI), is used for the photocatalytic C−H amination and C−N coupling of aromatic hydrocarbons under visible light irradiation. Owing to its highly positive potential of the valence band and the ability to temporary store electrons and charge‐compensating protons, K‐PHI mediates this reaction via multisite proton‐couple electron transfer (MS‐PCET).